Characterization of enteric bacteria from house flies in Health Campus, USM - Zainal, Sitti Nanda (2018)
Musca domestica, or known as house flies are synantrophic insect that play a role in being a mechanical vector in transmitting diseases. They are able to cause food contamination easily by landing on food, water or utensils. House flies have been associated with various pathogens, especially those that can cause food borne diseases such as cholerae, salmonellosis and shigellosis. Hence, this study was conducted to isolate and identify enteric bacteria from house flies collected from various locations in Health Campus, USM. Isolation and identification of bacteria was performed using conventional culture and identification methods. Total of 16 isolates as identified from six locations in the vicinity of Health Campus, USM which were three of the cafes; Harmoni, Murni and PPSK, sewage pond, garbage dumping site and animal house. Bacteria from genera Escherichia, Enterobacter, Klebsiella, Proteus and Serratia were identified. Both E. coli and Proteus spp. exhibited the highest number of isolates, n=5, respectively, followed by Enterobacter spp., n=3, Klebsiella spp., n=2 and Serratia sp., n=1. This study has confirmed the ability of house flies in carrying pathogenic enteric bacteria and may spread them into human habitations which have the possibility to cause food borne illnesses.